Asymptomatic maternal 3-methylcrotonylglycinuria detected by her unaffected baby's neonatal screening test - Sun Hee Lee; Yong Hee Hong (Korean Pediatric Society, 2014)
3-methylcrotonyl-coenzyme A carboxylase (3MCC) deficiency is an autosomal recessive disorder in which leucine catabolism is hampered, leading to increased urinary excretion of 3-methylcrotonylglycine. In addition, 3-hydroxyisovalerylcarnitine levels increase in the blood, and the elevated levels form the basis of neonatal screening. 3MCC deficiency symptoms are variable, ranging from neonatal onset with severe neurological abnormality to a normal, asymptomatic phenotype. Although 3MCC deficiency was previously considered to be rare, it has been found to be one of the most common metabolic disorders in newborns after the neonatal screening test using tandem mass spectrometry was introduced. Additionally, asymptomatic 3MCC deficient mothers have been identified due to abnormal results of unaffected baby's neonatal screening test. Some of the 3MCC-deficient mothers show symptoms such as fatigue, myopathy, or metabolic crisis with febrile illnesses. In the current study, we identified an asymptomatic 3MCC deficient mother when she showed abnormal results during a neonatal screening test of a healthy infant.